Bovine colostrum: benefits of its use in human food - SILVA,Emerson Gabriel dos Santos Oliveira (2019)
Abstract Colostrum is the first secretion of the mammary gland produced after birth, differentiating itself from mature milk because it has a higher concentration of proteins, immunoglobulins, vitamins, minerals, bactericides (lactoferrin, lysozyme and lactoperoxidase) and growth factors. The use of bovine colostrum for human consumption has been registered for many years in food or in medicinal therapies, and several studies have been conducted with the objective of evaluating its benefits in human food supplementation. The results point to improvements in cases of gastrointestinal, respiratory, inflammation, and bone development diseases, among others. Its commercialization currently takes place in physical or online markets in some countries. However, its commercialization for human consumption in Brazil is very recent, placing bovine colostrum as a new functional food option for consumers.